Research Trends of Augmented Reality E-Modules in Improving Students' Science Literacy: A Systematic Review - Rahmatia, Sulis; Ramdani, Agus; Artayasa, I Putu; Susilawati, Susilawati (Balai Publikasi Indonesia, 2025)
The rapid development of digital technology has driven transformations in educational practices, including in the presentation of science materials. This article presents a systematic review of research trends on augmented reality (AR)-based e-modules in the context of improving students' science literacy. This study aims to identify the direction of development, publication frequency, and thematic focus of research from 2016 to 2025. Data were collected through document searches on Google Scholar using relevant keywords, which were then analyzed to reveal the contribution of AR e-modules to science learning. The results of the analysis show a significant growth in interest in this topic, especially after 2020, along with the increasing need for interactive and contextual learning media. This study also maps the types of publications, years of publication, and the most widely used journals or proceedings. These findings reinforce the importance of developing AR-based e-modules as a potential learning strategy in improving conceptual understanding, scientific reasoning, and active involvement of students in the science learning process